Community-driven development: Treating poor people as partners - CGIAR Program on Collective Action and Property Rights (International Food Policy Research Institute, 2010)
Community-Driven Development (CDD) is an effective mechanism for poverty reduction, complementing market- and state-run activities by achieving immediate and lasting results at the grassroots level. Experience has shown that CDD can enhance sustainability and make poverty reduction efforts more responsive to demand. Well-designed CDD programs include the poor and vulnerable groups, build positive social capital, and give the poor greater voice both in their community and with government entities. CDD empowers poor people to decide for themselves and take charge of managing their community resources. Building on their institutions and resources, CDD treats poor people, not as targets of development, but as assets and partners in the development process.